Characteristics of Candidates for Allergen Immunotherapy. Issue 2 (September 2013) - Ciprandi, Giorgio; Incorvaia, Cristoforo; dell'Albani, Ilaria; Masieri, Simonetta; Cavaliere, Carmine; Puccinelli, Paola; Frati, Franco; ,
Allergic rhinitis (AR) may be cured by allergen immunotherapy (AIT). However, patient characteristics for prescribing AIT are not well defined. This study aimed at evaluating the patient's profile to be a candidate for AIT in a cohort of patients suffering from AR, evaluated in 20 Italian Allergy or Ear, Nose, and Throat Centers. The study has been performed on 198 patients (98 men; mean age, 26.8 years) with AR (assessed by Allergic Rhinitis and Its Impact on Asthma [ARIA] criteria). The kind and the number of prescribed allergen extracts, type of diagnosis, severity of symptoms, and patient's perception of symptoms and drug use were evaluated. Patients were subdivided in AIT-treated and without AIT (as controls) subgroups. Most of the patients (69.7%) had persistent AR with moderate–severe symptoms. The mean number of sensitization was 3.4. ARIA classification and sensitization number did not affect AIT choice, but the type of allergen was relevant. AIT-treated patients had milder symptoms than controls if assessed by doctors, but AIT patients perceived more severe symptoms and larger drug use than controls. This study shows that the choice of AIT is based on patient's perception and type of allergen, but number of sensitizations, symptom severity assessed by doctors, and ARIA classification are not relevant factors. The key message might be that it is always relevant to pay attention to the complaints referred by the patient.